Pharmacological profile of adenosine A2A receptors in patients with lower extremity peripheral artery disease and associated coronary artery disease: A pilot study. (15th June 2019) - Gaudry, Marine; Marlinge, Marion; Deharo, Pierre; Vairo, Donato; Bottone, Sarrah; Mottola, Giovanna; Kipson, Nathalie; Criado, Christine; Mace, Patrick; Chefrour, Mohamed; Benchaabane, Medhy; Magan, Celia; et al.
Abstract: Background: Altered blood flow occurs in patients with low extremity peripheral artery disease (LE-PAD). LE-PAD is mostly associated with coronary artery disease (CAD). Adenosine is an endogenous nucleoside that affects both coronary and limb artery blood flow, mostly via the adenosine A2A receptor (A2A R). We evaluated A2A R expression and function in peripheral blood mononuclear cells (PBMCs) and the femoral artery tissues of patients with LE-PAD. Methods: Artery tissues and PBMCs were sampled in 24 patients with intermittent claudication, and compared with PBMCs in 24 healthy subjects. Expression and function of A2A R was studied, using a A2A R monoclonal antibody with agonist properties, allowing determination of A2A R affinity (KD ) and cAMP production (ie.EC50 ). Results: A2A R expression on PBMCs was lower in patients than controls (median1.3 [range 0.6–1.8] vs 1.75 [1.45–2.1] arbitrary units; P  < 0.01), and correlated with A2A R expression in artery tissues (Pearson's r  = 0.71; P  < 0.01). Basal and maximally stimulated cAMP production of PBMCs was lower in patients vs controls: 172 [90–310] vs 244 [110–380] pg/10 6 cells ( P  < 0.05) and 375 [160–659] vs 670 [410–980] pg/10 6 cells ( P  < 0.05), respectively. A high KD /EC50 ratio, characteristic of spare receptors, was observed in CAD with inducible-myocardial-ischemia. Conclusion: A2A R expression in the arteries of patients, correlated with their expression in PBMCs. A2A R expression was lower in patients than in controls. A single blood sample (for measurement of A2A R expression on PBMCs) may help to screen patients with LE-PAD, whereas the presence of spare receptors may help with risk stratification before vascular surgery in CAD patients with high risk of myocardial ischemia. Graphical abstract: Unlabelled Image Highlights: LE-PAD is often underdiagnosed and is mostly associated with coronary artery disease (CAD). No biomarker is already available to evaluate both LE-PAD and associated CAD. Adenosine impacts coronary and lower limb blood flow, via A2A adenosine receptors. A2A R profile help to screen LE-PAD patients, especially those with associated severe CAD.